THE EFFECT OF THE DIRECT COMPOSITE VENEERS RESTORATIONS ON THE MICROBIAL STATUS OF ORAL CAVITY - Iamze Taboridze; Rusudan Ivanishvili (European Scientific Journal, ESJ, 2013)
The purpose of our research was to find out microbiological status of oral mucosa before and after veneering and the relation of bacterial complications of veneering with initial features of oral cavity, with general state of an organism, with social-biological factors and with bad habits.